Comparison of Deproteinization Methods Used Before TLC-DB and HPLC Analysis of Flumequine Residues in Milk - M. Choma, Irena; M. Grzelak, Edyta; Majer - Dziedzic, Barbara (Medicinal Chemistry, 2012)
Seventeen various extraction procedures based on precipitation of proteins in milk samples spiked with flumequine were tested. Several criteria were taken into account, when choosing the most effective. The supernatants were analyzed by thin-layer chromatography - direct bioautography (TLC-DB) and high performance liquid chromatography (HPLC-UV). The results obtained from both methods indicate as the best the same deproteinization procedure. The addition of acetonitrile to milk in 1:1 volume proportions gave the highest concentration of flumequine in supernatant and prompt coagulation of proteins in milk samples.
Keywords: proteins